Dancehall music and urban identities in Zimbabwe – a constructive postmodern perspective - Dube, Zorodzai (Hervormde teologiese studies, 2016)
Dancehall music may be seen as a commentary over the socio-political events that are unfolding in Zimbabwe since 2008, a period characterised by political and economic uncertainty. The study focuses on how this genre of music reflects identities that emerge from the context characterised by the disintegrating state institutions and fragile households. With such a context, dancehall music may be interpreted as offering hope and courage. Notably, the music carries a unique theological injunction where God is called upon to witness and offer strength, not to punish or change the status quo. I call this genre of music wilderness music to explain that the music provides spaces of hope and courage to fragile and less certain identities.